Castlesteads stone-paved area (Scottish Historical and Archaeological Internet Reports, 2010)
A scatter of chert and flint flakes noted during fieldwalking led to the discovery of a stone-paved area. This was associated with a feature interpreted as a soakaway 'sink'. Artefacts include part of a saddle quern, a small perforated sandstone pebble and a small group of undiagnostic lithics. Samples taken for palynological analysis were found to be unsuitable. The small size of the artefact assemblage and the lack of any close parallels make interpretation extremely difficult.